Proyecto de factibilidad para la creación de una productora de barras de chocolate instantáneo, para la ciudad de piñas, provincia el oro - Delgado Cueva, Marcos Vinicio (2024)
This project focuses on the feasibility for the creation of an instant chocolate bar manufacturer in the city of Piñas, with the aim of meeting the growing demand for quality and convenient chocolate products. Specific objectives were set, which included conducting a market study to determine supply and demand, preparing a technical and administrative study to define the installed capacity and organizational structure, as well as an economic and financial analysis to evaluate the profitability of the project. The methodology used consisted of surveys of local consumers, analysis of market data and evaluation of costs and benefits. The results revealed that 100% of the respondents considered the implementation of the production company viable, and 89% expressed a good opinion on the introduction of the product in the city. In addition, adequate installed capacity was identified and positive financial indicators were established, such as a favorable Net Present Value (NPV) and an attractive Internal Rate of Return (IRR). In conclusion, the project proved to be viable from both the market and the technical and financial point of view, suggesting that the creation of instant chocolate bar manufacturer in Piñas is not only possible, but can also be highly profitable. It is recommended to implement effective marketing strategies and maintain rigorous financial control to ensure the long-term success of the project.